Loss of PRDX6 Aborts Proliferative and Migratory Signaling in Hepatocarcinoma Cell Lines - Daniel J. Lagal; María J. López-Grueso; José R. Pedrajas; Thomas L. Leto; J. Antonio Bárcena; Raquel Requejo-Aguilar; C. Alicia Padilla (Antioxidants, 2023)
Peroxiredoxin 6 (PRDX6), the only mammalian 1-Cys member of the peroxiredoxin family, has peroxidase, phospholipase A2 (PLA2), and lysophosphatidylcholine (LPC) acyltransferase (LPCAT) activities. It has been associated with tumor progression and cancer metastasis, but the mechanisms involved are not clear. We constructed an SNU475 hepatocarcinoma cell line knockout for PRDX6 to study the processes of migration and invasiveness in these mesenchymal cells. They showed lipid peroxidation but inhibition of the NRF2 transcriptional regulator, mitochondrial dysfunction, metabolic reprogramming, an altered cytoskeleton, down-regulation of PCNA, and a diminished growth rate. LPC regulatory action was inhibited, indicating that loss of both the peroxidase and PLA2 activities of PRDX6 are involved. Upstream regulators MYC, ATF4, HNF4A, and HNF4G were activated. Despite AKT activation and GSK3β inhibition, the prosurvival pathway and the SNAI1-induced EMT program were aborted in the absence of PRDX6, as indicated by diminished migration and invasiveness, down-regulation of bottom-line markers of the EMT program, MMP2, cytoskeletal proteins, and triggering of the “cadherin switch”. These changes point to a role for PRDX6 in tumor development and metastasis, so it can be considered a candidate for antitumoral therapies.